Comparison of the Diagnostic Utility of Manual Screening and the ThinPrep Imaging System in Liquid-Based Cervical Cytology - Zühal ÖZCAN; Elife KIMILOĞLU; Ayşenur AKYILDIZ İĞDEM; Nusret ERDOĞAN (Federation of Turkish Pathology Societies, 2020)
Objective: To compare the diagnostic results of the ThinPrep manual method (TPMM) and ThinPrep automated method (TPAM) in liquid-based cytology and present the advantages and disadvantages of both methods. Material and Method: A total of 1.500 randomized ThinPrep Pap tests that were screened manually and archived in 2015 were reviewed by a blinded researcher manually and by the ThinPrep automatic method. Results: There was a 83.3% increase in the detection of ASCUS (Atypical squamous cells of undetermined significance) with the TPAM compared to the TPMM, and with respect to the reference results, the accuracy was higher for the TPAM than for the TPMM. We also noted a 33.3% increase in the rate of LSIL (Low grade squamous intraepithelial lesion) and 20% increase in the rate of HSIL (High grade squamous intraepithelial lesion) by the TPAM. Concordance was best between the TPAM and reference cytologic diagnoses. The sensitivity was higher for the TPAM and the specificity was similar for both methods. The false positive rate was higher for the TPAM than the TPMM but the false negative rate was higher for the TPMM. We determined a 30% gain in screening time per smear by the TPAM. However, rejection of many samples by the system, especially because of air bubbles, was a limitation of the TPAM. Conclusion: The TPAM has advantages over the TPMM as well as disadvantages such as limiting features and a high false positive rate. The TPAM should be supported by the manual method to decrease the false positive rate.